1993
DOI: 10.2307/3350407
|View full text |Cite
|
Sign up to set email alerts
|

Economic Incentives in the Choice between Vaginal Delivery and Cesarean Section

Abstract: The dramatic rise in cesarean-section (C-section) rates, and their high costs and wide variation, has raised interest in understanding the factors affecting decisions to use this procedure. The economic incentives of physicians, hospitals, payers, and mothers are examined. In the economic framework, physicians must balance their short-term interests against their reputation, which is derived from efficiently providing what mothers want. Providers who encounter higher opportunity costs while attending to mother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
3

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 70 publications
2
59
0
3
Order By: Relevance
“…27 Financial incentives for cesarean delivery may affect cesarean rates in certain systems. 28 At the LaFarge Birthing Center, there was no fi nancial incentive for operative delivery. Additionally, malpractice concerns may increase non-Amish cesarean rates.…”
Section: Cesarean Ratementioning
confidence: 99%
“…27 Financial incentives for cesarean delivery may affect cesarean rates in certain systems. 28 At the LaFarge Birthing Center, there was no fi nancial incentive for operative delivery. Additionally, malpractice concerns may increase non-Amish cesarean rates.…”
Section: Cesarean Ratementioning
confidence: 99%
“…From a policy perspective, one concern about the rise in the caesarean rate is the additional healthcare costs that it involves. Keeler and Brodie (1993) found that in 1989, the physician's charge alone was on average $500 more to perform a C-section than a vaginal birth. Gruber et al (1999) find that this difference depends on the patient's insurance status, with physicians receiving $561 more to perform a C-section for patients with private insurance and only $127 more for patients with Medicaid.…”
Section: Vbacs In the Usmentioning
confidence: 99%
“…Similarly, Stafford (1990) found that women with private insurance in California are more likely than HMO enrollees to receive a cesarean delivery. Keeler and Brodie (1993) suggest that economic incentives may play a role in cesarean deliveries. Women with private fee-for-service insurance have the greatest likelihood of cesarean deliveries due to a combination of the higher provider reimbursements and the low financial cost to women.…”
Section: Literaturementioning
confidence: 99%
“…They claim that physicians overused cesarean delivery relative to what would be chosen by a financially disinterested provider. In addition, Keeler and Brodie (1993) argue that women also have economic incentives to demand too many cesarean deliveries.…”
Section: Cesarean Deliverymentioning
confidence: 99%